2021
DOI: 10.1088/2053-1591/abe060
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and mechanical performances of bamboo strip

Abstract: Bamboo strips extracted from Phyllostachys viridiglaucescens, grown in Europe, were analysed to assess their thermal and mechanical properties for composites application. Thermal stability of the European bamboo was studied by Thermogravimetric Analysis (TGA) and compared to the one of species grown in Oceania. An evolution of the chemical composition along the radial direction of the Phyllostachys bamboo was identified by TGA. The inner part of culms shows a higher proportion of hemicelluloses, while the perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…On the high-temperature side, the increase of energy loss might have been due to the viscoelasticity of bamboo fibers. This hypothesis is supported by previous data recorded on bamboo strips obtained from the same bamboo species, reported by Richmond et al [56]: They observed by DMA in the tensile mode a viscoelastic relaxation peak at 200 °C.…”
Section: Tensile Loss Modulussupporting
confidence: 90%
“…On the high-temperature side, the increase of energy loss might have been due to the viscoelasticity of bamboo fibers. This hypothesis is supported by previous data recorded on bamboo strips obtained from the same bamboo species, reported by Richmond et al [56]: They observed by DMA in the tensile mode a viscoelastic relaxation peak at 200 °C.…”
Section: Tensile Loss Modulussupporting
confidence: 90%
“…This value is particularly high compared with the glassy modulus of the matrix (1.8±0.1 GPa). In a previous work, the Young's modulus of the same bamboo strips than the ones used in composites was measured : 10±2.4 GPa [34]. The major point on figure 9 is that, in the elongation mode, the contribution to the Young's modulus of the bamboo reinforcement is predominant.…”
Section: Dynamic Mechanical Analysis Of Bamboo Strips/epoxy In Tensile Modementioning
confidence: 92%
“…The restriction comes from the processing temperature, which is limited by the thermal stability of natural fibres. It has been shown that the temperature should be below 200 °C to avoid any thermal degradation of the natural reinforcements [34]. Such limitations favour thermosets.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations